Glycyl-L-histidyl-L-lysine-Cu2+ attenuates cigarette smoke-induced pulmonary emphysema and inflammation by reducing oxidative stress pathway - Zhang, Qin; Yan, Liming; Lu, Jingwen; Zhou, Xiaoming (Frontiers in Molecular Biosciences, 2022)
Background: Chronic obstructive pulmonary disease (COPD) is a common disease manifested by a persistent airflow limitation and characterized by chronic airway inflammation and lung emphysema. The cigarette smoke (CS)-induced inflammatory response and oxidative stress play essential roles in multiple cellular processes of COPD. Glycyl-L-histidyl-L-lysine (GHK) is a nontoxic and natural tripeptide involved in the process of healing and regeneration. With the combination of Cu(II), the tripeptide-copper complex glycyl-L-histidyl-L-lysine-Cu2+ (GHK-Cu) improve antioxidative and anti-inflammatory bioavailability, and they might offer potential therapeutic properties for COPD. Thus, this study aimed to explore the therapeutic effects of GHK-Cu on CS-induced emphysema. Methods: C57BL/6 mice were exposed to CS for 12 weeks to induce pulmonary emphysema. GHK-Cu was administered intraperitoneally (i.p.) at doses of 0.2, 2 and 20 µg/g/day in 100 µl of saline on alternative days from the 1st day after CS exposure. The effects of GHK-Cu on the morphology of CS-induced emphysema, the inflammatory response and oxidative stress were evaluated. We also assessed the antioxidative effect of GHK-Cu on human alveolar epithelial A549 cells. Results: GHK-Cu treatment attenuated the CS-induced emphysematous changes and partially reversed the MMP-9/TIMP-1 imbalance in the lung tissue. GHK-Cu alleviated the inflammatory response and oxidative stress by reducing the expression of TNF-α and IL-1β in the bronchoalveolar lavage fluid and the enzymatic activity of MPO and MDA in the lung homogenate while restoring the T-AOC and GSH content. Furthermore, GHK-Cu treatment reversed the CS-induced increase in NF-κB expression and increased the Nrf2 level, which is a component of the antioxidant defense system, in mice with chronic CS exposure. In CSE-exposed human alveolar epithelial A549 cells, GHK-Cu also inhibited oxidative stress by suppressing MDA levels and restoring T-AOC and GSH levels, which were modulated by upregulating Nrf2 expression. Conclusion: GHK-Cu treatment attenuated CS-induced emphysema by anti-inflammation by downregulating NF-κB and antioxidation via upregulation of the Nrf2/Keap1 pathway in lung tissues.